Pemanfaatan Media Sosial dan Pengaruhnya terhadap Prestasi Belajar PAI di SMA Kabupaten Pidie Jaya - Mulyana, Mulyana; Salami, Salami; Nurbayani, Nurbayani (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2024)
Education is defined as an effort undertaken by a person or group of people to become mature or reach a higher level of life or livelihood in a mental sense. Islamic education in the general sense is